Perkembangan Sosial Anak Usia 3-5 Tahun yang Paud dan Tanpa Paud di Desa Binakal Kecamatan Binakal Kabupaten Bondowoso - Rosalin, Vivin Febrianti; Zakiyah, Mutmainnah; Suhartin, Suhartin (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2024)
Early Childhood Education (ECE) is one of the efforts to enhance children's abilities, both in terms of intelligence and social behavior, including interaction as social beings. Social development is a crucial aspect of communal life, as without social skills, harmonious coexistence is not possible. This study aims to identify the differences in social development between children aged 3-5 years who attend ECE and those who do not in Binakal Village, Binakal Subdistrict, Bondowoso Regency. This comparative analysis research used a cross-sectional study design. The population consisted of all children aged 3-5 years in the area, with a total sampling technique resulting in 38 respondents. The research instrument was an observation sheet, and data analysis was conducted using the Mann-Whitney test. The analysis results indicated significant differences in social development between children who attend ECE and those who do not. This study is expected to enhance parents' understanding of the benefits of ECE in supporting their children's developmental process.